Entrepreneurship in parfum making for out-of-school youth - Cioco, Priscilla S. (2007)
Training modules on basic entrepreneurship and perfume-making were developed and validated in this action research. The training was conducted among thirty at-risk out-of-school-youth (OSY) aged 16-24 at a training center in a parish church in Quezon City. They were trained to make perfume, eau de toilette and eau de cologne for four days. This study aimed to catch the OSY before they become children in conflict in law (CICL) by providing needed intervention. Training on perfume making and entrepreneurship served as the SPED intervention for this group of OSY which enabled five of them to engage in business and be economicaly mainstreamed in the community.